Preparing Future-ready Learners: 21st Century Skills in an Open and Distance Learning Education in Malaysia - Ismail, Zulaihan; Che Aziz, Raziana; Chooi Chea, Chiam (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2024)
The 21st century requires a dynamic, flexible and highly skilled workforce to ensure that the sustainability of economic growth remains viable in a period of volatility, uncertainty, complexity and ambiguity. Furthermore, digitalization which is a driving force for economic growth in the 21st century has also changed the way of practice in every aspect of life and its rising significance could not be taken lightly. Education is no exception and has undergone significant changes over the years, such as the introduction of online learning compared to brick-and-mortar education, and the emergence and adoption of new technologies. Graduates produced by the education system must be globally competent and competitive for the 21st century. A transformative educational approach is needed to nurture an adaptive, inquisitive person with strong skills and values to meet the demands of the 21st century and beyond. It is vital to be future-ready in education moving away from the conventional teaching method. This paper aims to study the significance of 21st century skills in preparing future-ready learners in an open and distance learning (ODL) institution in Malaysia. The results of this paper could provide insights to the various stakeholders to formulate appropriate teaching and learning processes, to develop and nurture 21st century skills among graduates in ODL institutions while sustaining the economic growth in Malaysia.